Spread of Phytophthora cinnamomi in a naturally Infested Vineyard Soil - Maraisa, P. G.; Hattingh, M. J. (South African Journal of Enology and Viticulture, 2017)
Phytophthora cinnamomi Rands. was isolated from rootstocks of dead or diseased vines in vineyards from 14 districts in the Cape Province of South Africa. It was recovered in vineyard soil to a depth of 320 mm. Downhill spread of the pathogen was more rapid through a soil with a perched water table (Estcourt: Rosmead soil series) than through a freely draining soil (Clovelly: Blinkklip soil series). Lateral movement of the fungus through soil occurred to a limited extent. The disease potential index of newly ingested soil was usually higher than that of areas previously infested. The results indicated the danger of introducing P. cinnamomi to poorly drained soils by planting infected vines.